Sex-differences in initiation of renin-angiotensin system inhibitors in patients with type 2 diabetes diagnosed with albuminuria. (14th October 2021) - Malmborg, M; Carlson, N; Schmiegelow, M D S; Gerds, T; Schou, M; Kistorp, C; Torp-Pedersen, C; Gislason, G
Abstract: Background: Renin-angiotensin system inhibitors (RASi) are the preferred drug of choice in patients with type 2 diabetes (T2D) and albuminuria to prevent progression of chronic renal disease and cardiovascular complications. However, it is unknown whether sex-differences exist in the initiation of RASi in patients with T2D and albuminuria, and potential sex-differences in the effect of RASi on all-cause death in these patients remains untested. Purpose: To examine potential sex-differences in the initiation of RASi in patients with T2D and albuminuria, and secondly whether these sex-differences are associated with mortality risk. Methods: Using Danish nationwide registers, we included patients with their first albumin-creatinine ratio (ACR; index date) of ≥30 mg/g between 1 January 2014 and 20 March 2019 in patients with T2D with no prior end-stage renal disease, no acute renal failure within 90 days, and no claimed prescriptions of RASi within 15 years. We used multiple Cox regression to study the hazard ratio (HR; men vs women) of 30-day RASi initiation. In 30-day survivors, we used another multiple Cox regression to compare mortality between patients who initiated RASi and patients who did not yet initiate RASi. Reported were the sex-specific standardized 1-year risk differences for fixed comorbidity distribution according to RASi treatment. Results: In 20, 440 patients (44% women), 1, 190 men and 682 women initiated RASi treatment within 30 days after index. The adjusted rate of RASi initiation was higher in men compared to women (HR 1.34 [1.22; 1.48]). This association was observed regardless of hypertension (no: HR 1.35 [1.20; 1.52]; yes: HR 1.34 [1.14; 1.57]) and ACR-group ((30–300] mg/g: HR 1.35 [1.22; 1.49]; ≥300 mg/g: HR 1.30 [0.98; 1.73]), although borderline significant for ACR ≥300 mg/g (p=0.071). The association declined with descending estimated glomerular filtration rate (eGFR) and was not significant for eGFR group (15–60] (eGFR (90–120]: HR 1.45 [1.28; 1.65]; (60–90]: HR 1.25 [1.06; 1.47]; (15–60]: HR 1.07 [0.77; 1.48]). 30 days after index, 49 patients (37% women) had died, and 9 patients (33% women) had emigrated. In 30-day survivors, the standardized 1-year mortality risk was 1.9% [1.4; 2.4] in men who readily initiated RASi, and 3.3% [3.0; 3.7] in men who did not (absolute reduction: 1.5% [0.9; 2.0]). In contrast, the absolute reduction was not significant in women (0.1% [−0.5; 0.8]). Standardizing according to sex, the associated 1-year mortality risk was 3.4% [3.1; 3.7] in men without RASi, and 2.8% [2.5; 3.0] in women (absolute risk difference 0.6% [0.3; 0.9]). In contrast, men with RASi were borderline significantly associated with a lower 1-year mortality risk compared to women with RASi (absolute risk difference 0.8% [0.0; 1.5], p=0.042). Conclusions: In patients with T2D and albuminuria, men are more likely to initiate RASi within 30 days, and RASi appears to be associated with greater benefit on 1-year mortality risk in men. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation